(untitled) (UCC Law Journal, 2025)
This paper critically examines the applicability and relevance of Roscoe Pound’s sociological jurisprudence to the legal and educational systems of Ghana. It argues that while Ghana’s legal architecture is constitutionally sound and institutionally robust, it remains constrained by inherited colonial formalism, doctrinal rigidity, and cultural alienation. Drawing on Pound’s foundational thesis, law must function as a tool for social engineering rather than a self-contained doctrinal system. The paper assesses Ghana’s jurisprudential trajectory and identifies a critical need to align legal norms, practices, and education with the socio-cultural realities of the Ghanaian populace. Through a desktop methodology grounded in doctrinal analysis and comparative legal theory, the study interrogates the formalism in judicial reasoning, the marginalization of customary law, and the doctrinal orthodoxy prevalent in legal education. It proposes a sociologically informed legal reform agenda encompassing interdisciplinary legal education, empirical legal research, and context-sensitive judicial interpretation. The study finds that integrating local knowledge systems, advancing community-based legal pedagogy, and democratizing access to justice are essential for the evolution of a Ghanaian legal system that is equitable, dynamic, and culturally responsive.